1986
DOI: 10.1002/bjs.1800730215
|View full text |Cite
|
Sign up to set email alerts
|

Drainage in uncomplicated thyroid and parathyroid surgery

Abstract: A randomized study of the value of drainage in thyroid and parathyroid surgery is presented. Fifty patients were provided with surgical drains and another fifty patients were allocated to a control group without drainage. Complications were few in either group and the rate of subjective discomfort from the collar incision was equally low in both groups. The observations suggest that the provision of drainage is not necessary after uncomplicated neck surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0
5

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 1 publication
7
43
0
5
Order By: Relevance
“…The fact that wound infections developed in two of our patients in the drained group, supports the belief that drains predispose the area to infective complications (Ariyanayagam et al, 1993;Kristoffersson et al, 1986;Tabaqchali et al, 1999).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The fact that wound infections developed in two of our patients in the drained group, supports the belief that drains predispose the area to infective complications (Ariyanayagam et al, 1993;Kristoffersson et al, 1986;Tabaqchali et al, 1999).…”
Section: Resultssupporting
confidence: 83%
“…On the other hand, drain usage might be rejected in non-complicated cases because drainage is very low and might be not necessary, or because adequate haemostasis can never be replaceable by using drains; and in the case of incomplete drainage, seroma or hematoma would be the unavoidable conclusion (Karayacin et al, 1997;Peix et al, 1992;Ruark and Abdel-Misih, 1992). Or drains might be associated with possible infection (Ariyanayagam et al, 1993;Kristoffersson et al, 1986;Teboul et al, 1992). In addition, surgical techniques for benign thyroidal disorders have improved greatly over the past several years and postoperative morbidity and mortality rates have further decreased.…”
Section: Resultsmentioning
confidence: 99%
“…9,18 Few studies have observed infective complications with the use of drain, but we didn't find such associations with drain use in present study. 7,17,19 Author found decreased post-operative pain in group A (without drain) which has been already reported in previous few studies. 5,7 Because of reduced pain and less discomfort, author found decreased length of hospital stay in the non-drainage group without any morbidity.…”
Section: Discussionsupporting
confidence: 69%
“…11 Most of the studies in literature concluded that suction drain is not necessary for routine thyroid surgery and the similar result author have got in present study for hemithyroidectomy. 2,5,7,9,11,19 Hence author believe that hemithyroidectomies are also safe without drains and no added advantages in keeping drains in thyroid surgeries.…”
Section: Discussionmentioning
confidence: 97%
“…These studies, however, are prone to bias because of their retrospective or nonrandomized comparative design. Some randomized controlled trials were performed to solve this difficulty [6,26,27,28,29,30,31,32,33,34,35,36,37]. None of them were able to demonstrate statistically significant differences in the frequency of acute or late neck hematoma/seroma.…”
Section: Discussionmentioning
confidence: 99%